Synthetic Biology and Metabolic Engineering Employing Escherichia coli for C2–C6 Bioalcohol Production - Liang, Liya; Liu, Rongming; Freed, Emily F.; Eckert, Carrie A. (Frontiers in Bioengineering and Biotechnology, 2020)
Biofuel production from renewable and sustainable resources is playing an increasingly important role within the fuel industry. Among biofuels, bioethanol has been widely used as an additive for gasoline. Higher alcohols can be blended at a higher volume in gasoline compared to ethanol and generate lower greenhouse gas (GHG) emissions without changing current fuel infrastructures. These fuels have the potential to replace fossil fuels in support of more environmentally friendly processes. This review summarizes the efforts to enhance bioalcohol production in engineered Escherichia coli in the last five years, and analyzes the current challenges in increasing productivity for industrial application.